Remote Sensing and GIS Technology in Bangladesh For Environmental Monitoring A case Study (Journal of Environmental Science and Natural Resources, 2015)
Bangladesh is one of the disasters prone country faces Cyclones, Floods, draught, Norwesters/Tornadoes, Thunderstorm Earthquake etc. almost every year. Cyclones are the most devastating storm affecting Bangladesh, but there are other kinds of storm named Norwesters and Tornadoes. Storms characterized by strong surface wind exceed 100 miles per hour known as tornados. They are formed suddenly, usually on land and are extremely localized. Thunderstorm and Tornado occur in pre-monsoon season frequently in Bangladesh which cause lot destruction to lives and properties and hampers sustainable development. Norwesters come mainly from the north westerly direction (and hence the name) and are land based. They are a very common phenomenon in Bangladesh during late Chaitra and Baishak month and are known in Bengali as Kalbaishaki. The physical cause of this disaster is embodied in law of science and hence proper scientific research is necessary to deal with them.  The Role of Remote Sensing and GIS technology in monitoring of such natural disasters like tornado has been described in this paper.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22155 J. Environ. Sci. & Natural Resources, 7(1): 111-112 2014